Mechanisms of Change in a Group Career Exploration Intervention: The Case of “Bryan” - Kerner, Emily A.; Fitzpatrick, Marilyn R.; Rozworska, Karolina A.; Hutman, Heidi (Canadian Journal of Counselling and Psychotherapy, 2012)
This article presents the case of one 16-year-old male who failed a career exploration class and then participated in a group intervention designed to increase his motivation to explore. Using a case study method, the authors triangulated video, questionnaire, observational, interview, and artefact data to identify the main themes that emerged for the participant over the course of the intervention. Themes were integrated into a narrative of the participant’s process of developing self-determination for career exploration. Overall, the results suggest that interpersonal connection, structured activities, experiential learning, and participant resilience were all central mechanisms that contributed to change.